Geographical‐based variations in white truffle Tuber magnatum aroma is explained by quantitative differences in key volatile compounds. Issue 4 (10th March 2021) - Niimi, Jun; Deveau, Aurélie; Splivallo, Richard
Summary: The factors that vary the aroma of Tuber magnatum fruiting bodies are poorly understood. The study determined the headspace aroma composition, sensory aroma profiles, maturity and bacterial communities from T. magnatum originating from Italy, Croatia, Hungary, and Serbia, and tested if truffle aroma is dependent on provenance and if fruiting body volatiles are explained by maturity and/or bacterial communities. Headspace volatile profiles were determined using gas chromatography–mass spectrometry–olfactometry (GC‐MS‐O) and aroma of fruiting body extracts were sensorially assessed. Fruiting body maturity was estimated through spore melanisation. Bacterial community was determined using 16S rRNA amplicon sequencing. Main odour active compounds were present in all truffles but varied in concentration. Aroma of truffle extracts were sensorially discriminated by sites. However, volatile profiles of individual fruiting bodies varied more within sites than across geographic area, while maturity level did not play a role. Bacterial communities varied highly and were partially explained by provenance. A few rare bacterial operational taxonomical units associated with a select few nonodour active volatile compounds. Specificities of the aroma of T. magnatum truffles are more likely to be linked to individual properties than provenance. Some constituents of bacteria may provide biomarkers of provenance and be linked to nonodour active volatiles.